A Study of the Relationship between the Two Types of Crystallite Dislocation Density and the Particle Size of Barium Oxide (BaO) Nanoparticle - S. Abdul-Jabbar, Shefaa; H. Harbi, Khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The research is demonstrating the use of an X-ray diffraction pattern obtained experimentally from barium oxide powder. The X-ray diffraction pattern of the barium oxide nanoparticle sample was analyzed through the program to obtain the mean intensity width values and use these values to extract the particle size for all diffraction pattern lines using the Scherrer method. The nanoparticle size was calculated for each barium oxide line. Then the dislocation density was calculated through two mathematical equations, one of which depended on the particle size and the other depended on the integral breadth, a comparison was made between the results of the two dislocation densities and the particle size, where it was found that the dislocation density is inversely proportional to the particle size for both types, but the values of the dislocation density depend on the strain the retina will be bigger. Also, the relationship between the values of unit cell number and particle size was studied.